Comparing Models to Assess Creative and Critical Thinking in Vocational College Student - Wahyu Ridhoni; Punaji Setyosari; Dedi Kuswandi; Saida Ulfa (Edutechnium Journal of Educational Technology, 2025)
Creative and critical thinking are the two abilities required to grasp the opportunities and to upper-hand the challenges in the current digital era. Both complement each other. However, the assessments that involved both aspects of ability in one package are relatively limited. Further exploration is needed to develop new assessment model. The construction of the model begins with literary studies, develop, and try out the model. There are six constructions composed as the procedural framework, and another one for creative thinking: (C1) Parse, (C2) Deviate, and (C3) Modify, while the ones for critical thinking are : (C4) Verify, (C5) Compare, and (C6) Conclude. There are three assessment models that were feasible to be developed which refers to the 6 sub-variables: Self-Assessment, Multitype Objective Test, dan Problem Solving Case Study. The models have been tested on 32 informatics students, Hasnur Polytechnic, Indonesia. It turned out that the problem solving case study was no longer reliable, the best option were only Self-Assessment and Multitype Objective Test. The findings show that with Kruskal Wallis there are significant differences detected based on the assessment results among the models. So Multitype Objective Test is considered to be the best option.